Factor affecting transfer of training in public higher learning institution in southern region of Malaysia / Khairunnisa Rahman and Shafiee Md Tarmudi - Rahman, Khairunnisa; Md Tarmudi, Shafiee (2012)
Employee skills and motivation are critical factor for organizational success. This has always been true, as the modern change is drawing increased attention to the ways that human resource development activities can used to ensure that organization members have what it takes to successful meet their challenges. To meet these challenges the employees must be competent and many organizations are spending their budget every year for sending their employees for training. Competence workers can bring the organization to greater heights and besides that, it also helps to retain and grow skill to remain competitive. Training is the one of the learning processed that has arranged continuously to change knowledge, skill and attitude of the employees so that they will be competent. The successful training program will give the advantage for the organization and the workers. The successful of the training are based on what has been learned at the training program can be implemented at the workplace. Organization needs to ensure that transfer of training happened in the workplace. The purpose of this research is to identify the relationship between trainee characteristics (ability, motivation and personality) and organizational factor (technology support, organizational culture) towards transfer of training.